Nearing the Shore: The Mystery of Living While Dying - Guenter, Dale (Ars Medica, 2017)
As a family physician turning 50, I felt drawn into the question of what it would be like to befriend my own death. Diving into this exploration has led me to understand how much better my living can be, and how this understanding can become part of my work with patients.